EFEKTIVITAS MEDIA GAMBAR BERSERI PADA KETERAMPILAN MENULIS NARASI - Ningrum, Dhelia Anggita; Fardani, Much Arsyad; Fajrie, Nur (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
This research is motivated by shortcomings of habituation using Javanese language at school, and it is known that Javanese writing skills possessed by students are low. The aim of this research is to analyze the impact from application of serial picture media on writing Javanese narrative in third grade students. This research is a mixed research using quantitative techniques. The subject of this research is all third grade students from SD Pati Wetan 01 lasted from 3 meetings. Data collection techniques include observation, giving questions,   interviews, and documentation. Sample of this research totaling 31 students. The results show that there is a positive effective in use serialized picture media on students' Javanese narrative writing skills. This can be seen from the Paired Sample t Test which shows a significance value of 0.000. Because the significance value is less than 0.05. it is concluded that way study produces a significant effect in the application of serial image media on the skills of writing Javanese narrative learners.